Teachers’ Self-Efficacy in Teaching Students with Special Needs in Inclusive Primary Schools: A Phenomenological Study - Jesi Suryani Sitorus; Rahmah Fithriani; Ernita Daulay (Journal of General Education and Humanities, 2026)
This study explores English teachers’ self-efficacy in teaching students with special needs within inclusive primary school classrooms through a phenomenological approach. Inclusive education requires teachers to respond to diverse learning needs; therefore, teachers’ beliefs in their instructional capabilities are critical to the successful implementation of inclusive practices. This qualitative study was conducted in an inclusive primary school in Medan, Indonesia, involving ten English teachers who taught both inclusive and regular classes. Data were collected through the Teacher Efficacy for Inclusive Practices (TEIP) questionnaire and semi-structured interviews with three selected participants. The questionnaire provided an overview of teachers’ perceived self-efficacy levels, while the interviews captured teachers’ lived experiences of self-efficacy in inclusive teaching contexts. The interview data were analysed thematically, guided by Bandura’s self-efficacy theory. The findings indicate that English teachers generally demonstrate a high level of self-efficacy, which is shaped by mastery experiences in inclusive classrooms, professional collaboration, participation in professional development, and teachers’ ability to regulate their emotional responses when facing instructional challenges. Teachers with higher self-efficacy showed greater confidence and flexibility in implementing adaptive instructional strategies and managing diverse student needs. This study contributes to the literature by providing an in-depth phenomenological understanding of how English teachers construct and experience self-efficacy in inclusive primary education contexts.